Psychological change on inclusive educators through emotional regulation - Winarsunu, Tulus; Saraswati, Putri (Journal of Community Service and Empowerment, 2020)
Inclusive education requires special educators who have good abilities in regulating emotions. Psychoeducation helps educators regulate the emotions they feel. This activity aims to provide solutions to the obstacles faced and felt by special educators through emotional regulation psychoeducation. The psychoeducation activity was carried out in one of the inclusive schools in Batu City for a duration of 4 hours. The partner of this activity was a special educator teacher in an inclusion class in Batu City, they get material in the form of emotional regulation. They also have the opportunity to ask questions and answer and express their feelings during teaching. This activity was considered successful if the activity participants have a higher score after the activity (on the emotion regulation scale). Data analysis of the results of this activity was carried out by comparing the average scale score before and after the implementation of the activity using the excel program. The results of the activity showed that the psychoeducation that had been carried out was able to improve emotional regulation skills. After giving psychoeducation all participants (100%) had the ability to regulate emotions at a good level. Thus, this activity can improve emotional regulation skills.